Active vibration control of carbon nanotube reinforced composite beams. (December 2017) - Mirghaffari, Ali; Rahmani, Behrooz
In this paper, active vibration control of carbon nanotube reinforced composite beams subjected to a temperature rise is studied. For this purpose, piezoelectric patches are used as sensors to measure the displacement of the beam and as actuators to implement control forces. The governing equation of motion of this beam is derived from the Euler–Bernoulli theory and Hamilton's principle. Galerkin's method is utilized to obtain the temporal ordinary differential equations. An optimal observer-based output feedback controller is designed by the linear quadratic regulator ( LQR ) methodology to ensure closed-loop stability. Simulation studies demonstrate the effectiveness of the proposed method.